Studi Kelayakan Perencanaan Pembangunan Usaha Kesehatan Gigi Sekolah di SDN 1 Jagapura Wetan - Giovi, Antini Giovi Dwi Oktaviani; Heriyanto, Yonan; Octaviana, Devy; Hiranya Putri, Megananda (Jurnal Terapi Gigi dan Mulut, 2024)
School Dental Health Business (UKGS) is a program launched by the government that must be implemented and is an integral part of the School Health Business (UKS). UKGS services are carried out in a planned manner, for students, especially primary school students, within a certain period of time and are organized on an ongoing basis. The purpose of this study was to determine the feasibility of planning School Dental Health Business (UKGS) at SDN 1 Jagapura Wetan. The type of research used is qualitative with a focus interviewed design. The subjects selected to obtain information were the Head of the health center, the Principal, the School Committee and 9 parents of students. Information about infrastructure facilities, stated that SDN 1 Jagapura Wetan has 6 classes, there are UKS facilities, training on UKS has been held, already has a small doctor, has a good and clear water source, has an empty room to be used as UKGS, there is scheduled guidance from the puskesmas once a semester. The school also has an adequate source of electricity. Research that has been conducted regarding the Feasibility Study of UKGS Development Planning at SDN 1 Jagapura Wetan proves that SDN 1 Jagapura Wetan is feasible to establish UKGS because it has fulfilled the requirements for UKGS development and the responses given by informants received positive responses and agreed to establish UKGS. Conclusion: SDN 1 Jagapura Wetan deserves to establish UKGS because it has fulfilled the requirements for UKGS development.